Pervaporation Polyurethane Membranes Based on Hyperbranched Organoboron Polyols - Ilsiya M. Davletbaeva; Oleg O. Sazonov; Sergey E. Dulmaev; Alexander V. Klinov; Azat R. Fazlyev; Ruslan S. Davletbaev; Sergey V. Efimov; Vladimir V. Klochkov (Membranes, 2022)
On the basis of aminoethers of boric acid (AEBA), polyurethane vapor-permeable and pervaporative membranes were obtained. AEBAs, the structure of which is modified by bulk adducts (EM) of diphenylol propane diglycidyl ether and ethanolamine, were studied. It turned out that AEBA exists in the form of clusters, and the use of EM as a result of partial destruction of associative interactions leads to a significant decrease in the size of AEBA-EM particles and their viscosity compared to unmodified AEBA. The introduction of EM into the composition of AEBA leads to a threefold increase in the vapor permeability of polyurethanes obtained on their basis. The observed effect is explained by the fact that a decrease in the size of clusters leads to loosening of their dense packing. Areas of clustering due to associative interactions of hydroxyl groups, together with the hydrophilic nature of polyoxyethylene glycol, create channels through which water molecules can penetrate. The increase in vapor permeability is accompanied by a multiple increase in the permeability coefficients in the pervaporative dehydration of isopropanol.